1-2(3x-4)=5x-2(3x-5)

Simple and best practice solution for 1-2(3x-4)=5x-2(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-2(3x-4)=5x-2(3x-5) equation:


Simplifying
1 + -2(3x + -4) = 5x + -2(3x + -5)

Reorder the terms:
1 + -2(-4 + 3x) = 5x + -2(3x + -5)
1 + (-4 * -2 + 3x * -2) = 5x + -2(3x + -5)
1 + (8 + -6x) = 5x + -2(3x + -5)

Combine like terms: 1 + 8 = 9
9 + -6x = 5x + -2(3x + -5)

Reorder the terms:
9 + -6x = 5x + -2(-5 + 3x)
9 + -6x = 5x + (-5 * -2 + 3x * -2)
9 + -6x = 5x + (10 + -6x)

Reorder the terms:
9 + -6x = 10 + 5x + -6x

Combine like terms: 5x + -6x = -1x
9 + -6x = 10 + -1x

Solving
9 + -6x = 10 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
9 + -6x + x = 10 + -1x + x

Combine like terms: -6x + x = -5x
9 + -5x = 10 + -1x + x

Combine like terms: -1x + x = 0
9 + -5x = 10 + 0
9 + -5x = 10

Add '-9' to each side of the equation.
9 + -9 + -5x = 10 + -9

Combine like terms: 9 + -9 = 0
0 + -5x = 10 + -9
-5x = 10 + -9

Combine like terms: 10 + -9 = 1
-5x = 1

Divide each side by '-5'.
x = -0.2

Simplifying
x = -0.2

See similar equations:

| 1/2=-1/2x-6/5 | | -7/2+6/7x=-8/3 | | -2(3s-5)-10=-3(5s+3)-5 | | .24(18)+0.04x=0.08(24+x) | | 2r^2-6r/r-3 | | 5w^2+7w=6 | | 2p+7=5-(11p+6) | | 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 | | 3x+2x+2=9 | | 7822-3008= | | x^3-12x+35=0 | | 5k+24=k-8 | | 3x+14x+6=10 | | x-5=70 | | 9n^2+6n-3=3 | | 10x+13y=4620 | | 7/5+1/4t=5 | | 5x^2-5x-910=0 | | 4+4i/6-3i | | 7b-8=5b+4 | | -10x-19=-209 | | s=2X^2-10X+50 | | 6s^2-11s=35 | | UC=2X^2-10X+50 | | 6s^2+11s=35 | | 3y-8=6y+28 |

Equations solver categories